Public and Private Costs of the Clusterization Process - P. V. Tereliansky; S. Y. Soboleva; A. V. Sobolev (Управление)
The article is devoted to problems arising in the implementation of the state policy of forming economic clusters with the aim of improving the effectiveness of regional actors. The authors focus on the irrational behavior of market participants due to cognitive illusions and resulting variances in economic decision-making, leading to forced and unforced errors. The article also analyzes the public and private costs arising from the formation of cluster structures at the initiative of the state. The authors state the causes of occurrence of public costs that lead to negative economic effects, as well as proposed institutional arrangements for their removal or smoothing. It is also mentioned the difference in approaches to formation of cluster structures between the regional and federal authorities. The authors identify and describe the negative effects of clustering that occur at the regional level in the form of business-parasitism and business-symbiosis and lead to distortions in the clustering. These defects and distortions associated with deformation of regional institutional environment must be considered in the development and implementation of public policies for regional development and the formation of clusters. A comprehensive approach to the development of economic space taking into account all its levels is proposed.